Should Higher Education Be Subsidized More? - Koen Declercq; Erwin Ooghe (Center for Economic Studies and ifo Institute (CESifo), 2021)
Fiscal externalities arise if subsidies to higher education raise future net fiscal revenues. We investigate in which countries fiscal externalities provide a justification for increasing subsidies to higher education. First, we show that the marginal fiscal recovery rate, i.e. the ratio of the change in total net fiscal revenues and the change in total subsidy costs caused by a small change in tuition subsidies, is the key statistic: if larger than one, then a small increase in subsidies is unambiguously desirable. We also show that the marginal fiscal recovery rate depends on three sufficient statistics: the elasticity of participation with respect to subsidies, the success probability of the marginal student, and the ratio of the net fiscal revenue gain and the subsidy cost of a degree in tertiary education. Second, we use the sufficient statistics formula to approximate the marginal fiscal recovery rate in twenty OECD countries. The average marginal fiscal recovery rate is equal to 0.89, meaning that, on average, 0.89 euro is recovered of an increase in subsidies with one euro. This average hides substantial heterogeneity between countries. In six countries (Australia, Israel, the Netherlands, Ireland, the United Kingdom, and the United States), the marginal fiscal recovery rate is larger than one, implying that an increase in subsidies to higher education is unambiguously desirable in these countries. Third, to check the quality of our approximation, we also simulate the marginal fiscal recovery rate for one country (Belgium) on the basis of a more detailed model that allows for heterogeneity between students. Reassuringly, this simulation provides a roughly similar result than the approximation for this country. Moreover, the more detailed model allows for additional simulations (e.g., to compute a maximal tuition level) that are not feasible with the sufficient statistics formula.
Keywords: H23; I22; I26; 330; higher education; tuition subsidies; fiscal externalities; marginal fiscal recovery rate; maximal tuition